Succession Planning – An Intricate Phase in Talent Management System in Selected Organisations in Tamilnadu - Dr. S. Chandramohan, K. Santhanalaxmi (International Journal of Advanced Science and Technology, 2019)
In the world of technological up gradation, much of the things are getting mechanised yet human resource plays a major role in any type of organisation. Though the HR functions are carried out with the help of different software, recruiting the right talent and placing it in the suitable position can only be done with the human resource executives. The role of the manager did not end, after recruiting it continues with developing the talent of the workforce followed by succession planning. One of the complicate step in the talent management system is the succession planning. It benefits not only the individual but also the organisation in retaining the talented employees. The companies just focus on the other phases of talent management system and failed to concentrate on the succession management, as this phase identified the abled employee who perfectly suits with the desired job at an affordable cost. The study focuses on the process of succession planning, different practices of succession management, how organisations carry out the function as a part of talent management and the difficulties faced by them while implementing the phase. The research has been carry out in various organisations of diverse sectors and the respondents are the HR managers who are responsible for the successful succession management. The industries include BPO, automobile, hotels, hospitals, IT and others in different districts of Tamilnadu. Distinct statistical tools such as descriptive statistics, regression, t-test are used for identifying the importance of the succession planning and the complexities in execute the process. The study concludes that succession management is one of the challenging tasks for the HR managers and also a reason for the employees’ retentiveness towards their organisation.